Poetyka paradoksu w prozie Zygmunta Krzyżanowskiego - Gołubkow, Siergiej (Studia Rossica Posnaniensia, 2012)
The article deals with the poetics of paradox in the stories of Sigizmund Krzhizhanowsky, which were written in the years 1920–1930. The paradox of the writer served as an analytical tool to reveal the absurdity of Russian reality of that time. The novelist undermines imaginary quantities, to which too much importance was attached in the era of totalitarianism.